2018
DOI: 10.4111/icu.2018.59.2.91
|View full text |Cite
|
Sign up to set email alerts
|

What do patients with urothelial cancer know about the association of their tumor disease with smoking habits? Results of a German survey study

Abstract: PurposeSmoking represents a primary risk factor for the development of urothelial carcinoma (UC) and a relevant factor impacting UC-specific prognosis. Data on the accordant knowledge of UC-patients in this regard and the significance of physicians in the education of UC-patients is limited.Materials and MethodsEighty-eight UC-patients were enrolled in a 23-items-survey-study aimed to analyse patient knowledge and awareness of their tumor disease with smoking along with physician smoking cessation counselling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Almost 50% of our patients with primary NMIBC were current smokers and 35% of them definitively stopped, with a smoking cessation rate higher than that reported by other authors [17,18].In a retrospective cohort study, Koshiaris et al [17] found a 21% smoking cessation rate among bladder cancer patients, which is lower than the 27 and 29% detected among upper aerodigestive tract cancer and lung cancer patients, respectively. In a recent German survey, only 33% of the active smokers with a primary diagnosis of NMIBC had been prompted to quit smoking [18]. These data implicate the inadequacy of patients' counseling about cigarette smoking and suggest the need for a more active role of the urologists to increase the smoking cessation rate at diagnosis [19][20][21].…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Almost 50% of our patients with primary NMIBC were current smokers and 35% of them definitively stopped, with a smoking cessation rate higher than that reported by other authors [17,18].In a retrospective cohort study, Koshiaris et al [17] found a 21% smoking cessation rate among bladder cancer patients, which is lower than the 27 and 29% detected among upper aerodigestive tract cancer and lung cancer patients, respectively. In a recent German survey, only 33% of the active smokers with a primary diagnosis of NMIBC had been prompted to quit smoking [18]. These data implicate the inadequacy of patients' counseling about cigarette smoking and suggest the need for a more active role of the urologists to increase the smoking cessation rate at diagnosis [19][20][21].…”
Section: Discussionmentioning
confidence: 49%
“…The authors concluded that smoking cessation after diagnosis did not decrease the risk of recurrence compared to continuing smokers, but the power of the statistical analysis is limited by the small number of ex-smokers [16]. Almost 50% of our patients with primary NMIBC were current smokers and 35% of them definitively stopped, with a smoking cessation rate higher than that reported by other authors [17,18].In a retrospective cohort study, Koshiaris et al [17] found a 21% smoking cessation rate among bladder cancer patients, which is lower than the 27 and 29% detected among upper aerodigestive tract cancer and lung cancer patients, respectively. In a recent German survey, only 33% of the active smokers with a primary diagnosis of NMIBC had been prompted to quit smoking [18].…”
Section: Discussionmentioning
confidence: 61%
“…According to the estimations of World Health Organization in 2013, six million people worldwide died from the diseases caused by smoking including cancer, cardiovascular diseases and pulmonary diseases. [8] Cigarette smoking and occupational exposure are the main risk factors for urothelial carcinoma. In urinary bladder cancer (UBC), cigarette smoking is responsible for about one-third of all diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Only limited studies have shown the communication between patients and their physicians regarding their disease and smoking as well as the awareness and knowledge of UBC patients about the influence of smoking regarding their primary cancer diseases. [8] In this study we aimed to investigate the UBC patients with their history of smoking (tobacco exposure) and to find out the answer for their attitudes and awareness of the exposure -cancer relationship. Moreover, we aimed to show the association between smoking status with the stage, grade and histopathology of the tumoral disease.…”
Section: Introductionmentioning
confidence: 99%
“…Passive Smoking Cessation Rates A total of 21 studies reported passive smoking cessation outcomes (quit rates in the absence of a directed, active intervention) after the diagnosis of a urological cancer (3,669 patients). 19 Of these studies, 17 (81%) included patients with bladder cancer, 7 of which included patients with nonmuscle invasive bladder cancer exclusively. There was wide variation in smoking cessation rates after diagnosis with 14.3% to 79.0% of included adults reporting quitting at some time point after diagnosis (table 3).…”
Section: Smoking Cessation Interventions and Outcomesmentioning
confidence: 99%